Trypanosoma cruzi Affects Rhodnius prolixus Lipid Metabolism During Acute Infection - Sousa, Géssica; de Carvalho, Stephanie Serafim; Atella, Georgia Correa (Frontiers in Tropical Diseases, 2021)
The interaction between Rhodnius prolixus and Trypanosoma cruzi has huge medical importance because it responds to the transmission of Chagas disease, a neglected tropical disease that affects about eight million people worldwide. It is known that trypanosomatid pathogens depend on active lipid endocytosis from the insect host to meet growth and differentiation requirements. However, until now, knowledge on how the parasite affects the lipid physiology of individual insect organs was largely unknown. Herein, the biochemical and molecular dynamics of the triatomine R. prolixus lipid metabolism in response to T. cruzi acute infection were investigated. A qRT-PCR approach was used to determine the expression profile of 12 protein-coding genes involved in R. prolixus lipid physiology. In addition, microscopic and biochemical assays revealed the lipid droplet profile and the levels of the different identified lipid classes. Finally, spectrometry analyses were used to determine fatty acid and sterol composition and their modulation towards the infection. T. cruzi infection downregulated the transcript levels of protein-coding genes for lipid biosynthetic and degrading pathways in individual triatomine organs. On the other hand, upregulation of lipid receptor transcripts indicates an attempt to capture more lipids from hemolymphatic lipoproteins. Consequently, several lipid classes (such as monoacylglycerol, diacylglycerol, triacylglycerol, cholesteryl ester, phosphatidylcholine, and phosphatidylethanolamine) were involved in the response to the parasite challenge, although modulating only the insect fat body. T. cruzi never leaves the insect gut and yet it modulates non-infected tissues, suggesting that the association between the parasite and the vector organs is reached by cell signaling molecules. This hypothesis raises several intriguing issues to inspire future studies in the parasite-vector interaction field.